Welding analysis and optimization of ultra- sonic welding in HDPE-5%PBI composite by CODAS decision-making approach. (1st September 2022) - Ramesh, M; Panneerselvam, K
Abstract: Engineering plastics are increasingly being used in structural and non-structural applications. As the need for plastics grows, so do the joining requirements. Ultrasonic welding is one of the favoured processes for polymer composites among numerous approaches, especially for bonding plates, automotive panel boards and couplings due to its joint quality and low cost. The High-density polyethylene (HDPE) matrix was reinforced with 5 wt% of polybenzimidazole (PBI) fibre by twin screw extrusion process and welding samples were prepared using injection moulding. In this study, Ultrasonic welding was used to connect 4 mm-thick lapped HDPE-5wt% PBI composites. Taguchi-based L27 orthogonal array was employed for experiments to study the lateral shear strength (LSS) and Shore-D-Hardness for the input parameters (i) weld duration (30, 45 and 60 ms), (ii) frequency (19, 20 and 21 Hz) and (iii) horn pressure (1.5, 2 and 2.5 MPa). The relevance of the parameters affecting shear strength and hardness of weld was studied using analysis of variance (ANOVA). ANOVA results shows the frequency (Hz) and weld time (ms) had contributed 32.4% and 31.6% in determining shear strength and weld time (ms) contributes 45% for shore D hardness. The ultrasonic welding process was carried out, and the multi-criteria decision-making (MCDM) approach was used to optimise the process parameters. From CODAS assessment the relative evaluation score of 2.444 was achieved by the twenty fifth experiment having the input parameters (IP) at 60 ms welding time, frequency of 21 Hz and pressure at 2.5 MPa considering each output factor with an entropy of 0.5. Fractography and weld morphology of welded joints were investigated using scanning electron microscope (SEM).